Assessment of Central Retinal Sensitivity Employing Two Types of Microperimetry Devices - Liu, Hongting (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE: To compare the retinal sensitivity measurements obtained with two microperimeters, the Micro-Perimeter 1 (MP-1) and the Optos optical coherence tomography (OCT)/scanning laser ophthalmoscope (SLO) in subjects with and without maculopathies. METHODS: Forty-five eyes with no known ocular disease and 47 eyes with maculopathies were examined using both microperimeters. A contrast-adjusted scale was applied to resolve the different stimuli and background luminance existing between the two devices. RESULTS: There was a strong ceiling effect with the MP-1 in the healthy group, with 90.1% (1136 of 1260) test points clustered at 20 dB. The mean sensitivity for the corresponding points in the OCT/SLO was 25.8 ± 1.9 dB. A floor effect was also observed with the OCT/SLO in the maculopathy group with 9.7% (128 of 1316) points clustered at 9-dB values. The corresponding mean sensitivity in the MP-1 was 1.7 ± 3.9 dB. A regression equation between the two microperimeters was established in the common 10 to19 dB intervals as: OCT/SLO = 15.6 + 0.564 × MP-1 − 0.009 × MP-1(2) + k (k is an individual point constant; MP-1 coefficient P < 0.001; MP-1(2) coefficient P = 0.006). CONCLUSION: The OCT/SLO and the MP-1 provide two different ranges of contrasts for microperimetry examination. Broadening the dynamic range may minimize the constraint of the ceiling and floor effect. There is a significant mathematical relationship in the common interval of the contrast scale. TRANSLATIONAL RELEVANCE: Applying a unified and broadened dynamic range in different types of microperimeters will help to generate consistent clinical reference for measurements.